Local structure and ionic transport in acceptor-doped layered perovskite BaLa2In2O7 - Nataliia A. Tarasova (Chimica Techno Acta)
Materials with perovskite or perovskite-related structure have many applications because of theirs different physical and chemical properties. These applications are extremely diverse and cover different fields including hydrogen energy. Layered perovskites with Ruddlesden-Popper structure constitute a novel class of ionic conductors. In this paper, the effect of acceptor doping on the local structure and its relationship with transport properties were shown for layered perovskites based on BaLa2In2O7 for the first time. The geometric factor (the increase in the unit cell volume due to the increase in the ionic radii of cations) plays major role in the area of small dopant concentration (x  0.15). The concentration factor (the increase in the oxygen vacancy concentration) is more significant in the area of big dopant concentration (x  0.15). The acceptor doping is a promising way of improving the oxygen-ionic conductivity of layered perovskite BaLa2In2O7.